The Influence of Promotional Strategies on Sales of Household Appliances at the Hakasima Company, Lampung Branch 7 - Pradita, Resilia; Kusworo, Ahmad Dzulfikri Budi (Indonesian Journal Publisher, 2024)
Hakasima is a cooking equipment and household appliance provider company that distributes products directly from Korea, Europe and China. Hakasima Lampung 7 is a subsidiary of PD Sinar Mas. A decrease in the number of sales in a certain period has an impact on sales targets. The main objective of this study to learn more about the impact of promotional strategies on increasing sales on Hakasima Lampung 7. Using quantitative methods with 20 population sample and using Likert scale as data collection techniques with the scale of 1-5 points. Data processing with the SPSS 27 software and multiple linear regression testing. The findings indicate that Y = 1.093 + 0.191 (X1) + 0.563 (X2) promotional strategies and sales work well, and have positive impact. Particularly, promotional and sales strategies have a significant impact on total sales amount. Consider to the f test = Fcount 24.258 ≥ 0.05%, it represents acceptance, which indicating that it has a significant impact. R Square final value shows 0.741 or 74.1%, indicates that the sales strategy carried out at the Hakasima Lampung 7 can be explained by factors related to promotional and sales strategy variables, with the majority of the remaining 25.9% being impacted by any factor that is not addressed in this research.